2023
DOI: 10.12998/wjcc.v11.i5.1115
|View full text |Cite
|
Sign up to set email alerts
|

Envafolimab combined with chemotherapy in the treatment of combined small cell lung cancer: A case report

Abstract: BACKGROUND Combined small cell lung cancer (C-SCLC) is a special subtype of small cell lung cancer that is relatively rare, aggressive, and prone to early metastasis and has a poor prognosis. Currently, there are limited studies on C-SCLC, and there is no uniform standard treatment, especially for extensive C-SCLC, which still faces great challenges. In recent years, the development and progress of immunotherapy have provided more possibilities for the treatment of C-SCLC. We used immunotherapy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…The dose of XAPI was 4~80 mL/day, the course of treatment was 1 to 4 cycles. In these studies, the most common schemes are gemcitabine + cisplatin, [18–22,29,31–37,39] taxol + cisplatin [26–28,30,36,40] and navelbine + cisplatin [23,33–36] schemes. According to the pathological TNM staging of NSCLC, all the patients included in the study were III to IV stage diseases.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The dose of XAPI was 4~80 mL/day, the course of treatment was 1 to 4 cycles. In these studies, the most common schemes are gemcitabine + cisplatin, [18–22,29,31–37,39] taxol + cisplatin [26–28,30,36,40] and navelbine + cisplatin [23,33–36] schemes. According to the pathological TNM staging of NSCLC, all the patients included in the study were III to IV stage diseases.…”
Section: Resultsmentioning
confidence: 99%
“…In the included studies, 27 trials [13–28,30–40] reported the ORR of the 2 groups, a total of 1947 patients, including the treatment group (n = 973) and the control group (n = 974). There was no statistical difference between the studies ( P = .97 and I 2 = 0.0%), so the fixed effect model was used.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations